2015
DOI: 10.2500/ajra.2015.29.4153
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Metaanalysis of Middle Meatal Packing after Endoscopic Sinus Surgery

Abstract: This systematic review and metaanalysis suggests that use of middle meatal packing does not significantly reduce the risk of synechiae formation after ESS. There was, however, significant heterogeneity of the data analyzed, and the difference between groups was just short of statistical significance in our metaanalysis. Additional prospective randomized studies on this topic will further elucidate the utility of middle meatal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…We hypothesized that this was to prevent adhesion to the lateral wall and/or obstruction of the osteomeatal complex or perhaps was removed among a dense clutch of polyps. The former issue is important to avoid, but, rather than resecting the middle turbinate (and hence altering the anatomic appearance), we would advocate the placement of a middle meatal “spacer” at the end of the procedure 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that this was to prevent adhesion to the lateral wall and/or obstruction of the osteomeatal complex or perhaps was removed among a dense clutch of polyps. The former issue is important to avoid, but, rather than resecting the middle turbinate (and hence altering the anatomic appearance), we would advocate the placement of a middle meatal “spacer” at the end of the procedure 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis by Hobson et al, the pooled data revealed that 19.95% of patients with packing had synechiae compared to 36.6% in patients without packing. This difference however, did not reach statistical significance . Another meta‐analysis by Yan et al found no difference in synechiae formation rate between biodegradable nasal packing compared to no packing .…”
Section: Discussionmentioning
confidence: 95%
“…Whether to pack or not pack the middle meatus has been a question of interest for years. One systematic review and meta‐analysis by Hobson et al . evaluated various packing types vs control patients without packing.…”
Section: Discussionmentioning
confidence: 99%
“…Whether to pack or not pack the middle meatus has been a question of interest for years. One systematic review and meta-analysis by Hobson et al 28 evaluated various packing types vs control patients without packing. They noted that although there was a trend favoring packing, it was only marginally significant (p = 0.052), owing largely to the significant heterogeneity in study designs and data collected.…”
Section: Discussionmentioning
confidence: 99%